Das Modul Werbeslogans. Eine korpusinformierte lexikografische Ressource zum aktuellen Gebrauch von Werbeslogans außerhalb der Domäne Werbung - Polajnar, Janja (Lexikos, 2021)
E-Module Werbeslogans. A Corpus Informed Lexicographic Ressource of Advertising Slogan Use Outside the Domain of Advertising. The article aims to describe the development of E-Module Werbeslogans, integrated into OWID-Sprichwörterbuch at the Leibniz Institute for German Language in Mannheim. It represents a corpus informed online description and presentation of advertising slogans, i.e. set sentences from advertising, currently used outside the domain of advertising in everyday language. As these advertising slogans are used in the same way as proverbs, they can be similarly lexicographically described. The module is based on the lexicographic concepts developed in the EU project SprichWort. Eine Internetplattform für das Sprachenlernen für die Sprichwort-Plattform as well as the proverb articles in the OWID-Sprichwörterbuch; it is innovative and does not represent a continuation of traditional dictionaries in the field of phraseology. The article describes the corpus informed method for the analysis of advertising slogans used outside of the domain advertising, continues with the description of the lexicographic process as well as the microstructure of online slogan articles and concludes with the links that connect different information at the macrostructural level of OWID (Online-Wortschatz-Informationssystem Deutsch).